Peran Panti Jompo dalam Upaya Memenuhi Kebahagiaan Kepada Lansia: Studi Wacana di Panti Jompo Anugerah Pematang Siantar - Anggun Kabeakan; Haposan Silalahi; Priska Manullang; Meditatio Situmorang; Junjungan Simorangkir (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
The purpose of this study is to understand the role of Panti Jompo Anugrah Pematang Siantar in achieving the happiness of the elderly. Nursing homes are very important to provide a safe environment and adequate care to improve the quality of life of the elderly, because they often face various social and emotional challenges. The interactions, conversations, and narratives among the elderly, workers, and the head of the foundation were analyzed in this study through discourse studies. This study was conducted with a qualitative approach and used participant observation, in-depth interviews, and documentation. This study involved the elderly living in Panti Jompo Anugrah Pematang Siantar, nursing home employees, and the head of the foundation. This study is expected to provide a better understanding of the role of nursing homes in fulfilling the happiness of the elderly. The results are also expected to help related parties, including the government, elderly care institutions, and the general public, develop more efficient ways to improve the quality of life of the elderly living in nursing homes.